Sustaining interest: are green values converting to votes?. (28th July 2005) - Patulny, Roger; Norris, Kate
Sustainability is fashionable and becoming more important to the general policy discourse on protecting the environment. However, despite the government's adoption of a National Strategy for Ecologically Sustainable Development some 12 years ago, Australia's performance on crucial items such as emissions of carbon dioxide equivalents remains poor. Arguably then, for the environmental cause to be advanced substantially, not only must people's attitudes toward protecting the environment change, but also their voting intentions so as to send a signal to the major political parties. This paper presents internationally comparative research using data from the most recent waves of the World Values Survey. Changes in preferences associated with support for the environment are contrasted against changes in intentions to vote for Green political parties. Results indicate the strength and direction of the Green movement, and highlight gaps in the conversion of environmental values into votes.